EFEKTIVITAS PROSEDUR REKRUTMEN PEGAWAI NEGERI SIPIL DI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KOTA MANADO - BOLANG, IRENE PAULINA; OGOTAN, MARTHA; KOLONDAM, HELLY (JURNAL ADMINISTRASI PUBLIK, 2019)
Employee recruitment is the process of finding, finding and attracting suitable applicants tobecome employees within and by an agency. To obtain quality human resources with the amount that suitsyour needs, a recruitment method is needed that can be used in the withdrawal process based on a trulymature plan. Recruitment as a process of collecting prospective office holders in government agencies thatare in accordance with human resources to occupy a position in the employment function. The method thathas been developed by BKN in the recruitment and selection process is a competency-based recruitmentsystem using the Computer Assisted Test (CAT) method which is a refinement of the current recruitmentsystem. Computer Assisted Test (CAT) has many advantages including test participants can registerthemselves through the internet, test participants can be assessed directly according to the results obtained,the computer provides all the basic competency questions (general knowledge tests, scholastic aptitude tests,and maturity scale tests), the assessment is carried out objectively, the examinee can easily access the score(score) obtained. Another advantage of the use of Computer Assisted Test (CAT) in the selection process isthat the results obtained are more valid, minimize the possibility of corruption, collusion and nepotism, andreduce all forms of fraud. This study uses a type of qualitative research in which this research is descriptive,namely conducting in-depth interviews of primary data collection and secondary data collection, which thenresults of primary and secondary data is processed and data will be obtained. The results of the study broadlyindicate that the recruitment procedures carried out by the Manpower and Human Resources DevelopmentAgency of the City of Manado have been effective and in accordance with the initial purpose ofimplementing the CAT system, namely, to eliminate all forms of fraud during the recruitment process ofCivil Servants. It is hoped that the Human Resources Development and Human Resources Agency of theCity of Manado will continue to maintain and improve its performance so that further recruitment can runwell and can screen Civil Servants who are truly competent in their field.Keywords: Effectiveness, Recruitment, Procedure.